Analisis Pengaruh Kualitas Layanan pada Kepuasan dan Loyalitas Pengguna Website E-Meterai menggunakan Model E-S-Qual dan E-RecS-Qual (Studi Kasus: Mahasiswa Universitas Brawijaya) - Fauzan Zuhdi Wiryawan; Intan Sartika Eris Maghfiroh; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The E-Meterai website is a site that is shaded by Perum Peruri as a Digital Business Solution which provides services in the form of purchasing electronic stamps and affixing electronic stamps to documents. However, this website still encounters complaints regarding the number of stamps that do not match, the frequent occurrence of network errors, and the location of the stamps that do not match. For this reason, it is necessary to conduct research to find out how service quality affects the satisfaction and loyalty of E-Semite website users. In this study using quantitative methods using the model of Electronic Service Quality and Electronic Recovery Service Quality. The population used in the study were Brawijaya University students by including 100 samples of E-Meterai website users. In this study, the sample was taken using purposive sampling technique and multiple linear regression analysis and simple linear regression analysis as data analysis techniques. The results showed that the E-S-Qual and E-RecS-Qual variables had a partial (individual) and simultaneous (together) influence on customer satisfaction on the E-Meterai website. It was found that the E-S-Qual variable had a positive effect of 0.151 on customer satisfaction, the E-RecS-Qual variable had a positive effect of 0.153 on customer satisfaction and customer satisfaction had a positive effect of 0.748 on user loyalty on the E-Meterai website.